Pilotażowe studium oceny społecznego odbioru usług ekosystemowych świadczonych przez lasy wokół dużej aglomeracji miejskiej - Szast, Mateusz; Gielec, Renata; Likus-Cieślik, Justyna; Pietrzykowski, Marcin (Leśne Prace Badawcze, 2025)
The aim of this study was to analyse the public’s perception and expectations of the ecosystem services provided by forests near a large urban agglomeration. The study was conducted in a selected forest district of the Polish State Forest Administration (PGL Lasy Państwowe) among 129 respondents. Three groups of respondents were selected: the local community (43 people), comprising inhabitants living in the vicinity of the forest district; the forest district employees (13 people), who are directly involved with forest management; and forestry students (73 people). Among the forestry students and the local community, the rejection of hypothetical rationing and payment for forest access was expressed. The need to intensify activities to develop forest ecosystem services, especially cultural services, was also clearly formulated. The group of respondents mainly involved in forest management expressed an understanding of provisioning services (i.e., productive aspects) but also considered nonproductive needs (cultural services). Despite the differences between the preferences and opinions of respondents from the three groups surveyed, an appreciation and need for effective management of forests and their natural resources – while making their values accessible to the public – was identified. Among the forest district employees and the forestry students, there was support for wood as an energy resource and a high demand for this raw material. In contrast, the local community was much more likely to indicate the use of other sources of heating energy (natural gas, electricity, heat pumps). The study revealed that respondents from the local community knew relatively little about forest ecosystem services. As expected, the highest level of knowledge and awareness of forest ecosystem services was shown by the forestry students surveyed.